2006
DOI: 10.1111/j.1365-2958.2006.05274.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine peptidases CPA and CPB are vital for autophagy and differentiation in Leishmania mexicana

Abstract: SummaryIn the past, ultrastructural investigations of Leishmania mexicana amastigotes revealed structures that were tentatively identified as autophagosomes. This study has now provided definitive data that autophagy occurs in the parasite during differentiation both to metacyclic promastigotes and to amastigotes, autophagosomes being particularly numerous during metacyclic to amastigote form transformation. Moreover, the results demonstrate that inhibiting two major lysosomal cysteine peptidases (CPA and CPB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
182
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 77 publications
6
182
1
7
Order By: Relevance
“…Moreover, CPA and CPB from Leishmania mexicana were recently found to be essential for both autophagosome degradation and differentiation of that parasite. In addition, LmAtg4.2 was suggested to be involved in autophagosome formation, thus being upstream of CPA and CPB (39,46).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CPA and CPB from Leishmania mexicana were recently found to be essential for both autophagosome degradation and differentiation of that parasite. In addition, LmAtg4.2 was suggested to be involved in autophagosome formation, thus being upstream of CPA and CPB (39,46).…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization showed that Leishmania expressing GFP-ATG8 form GFP-labeled puncta corresponding to autophagosomes and that autophagy is induced by starvation, as in yeast and mammals, as well as increasing during differentiation. 20,21 During procyclic to metacyclic promastigote differentiation, GFP-ATG8 appears in tubular structures resembling the MVT-lysosome and the PEconjugated form of ATG8 is more abundant as shown by western blotting. Leishmania with defects in the autophagy pathway, either overexpressing a dominant-negative VPS4, important in endosomal sorting pathways, 21 or lacking the major lysosomal peptidases CPA and CPB, 20 are unable to fully differentiate, in addition to being unable to survive prolonged starvation.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 During procyclic to metacyclic promastigote differentiation, GFP-ATG8 appears in tubular structures resembling the MVT-lysosome and the PEconjugated form of ATG8 is more abundant as shown by western blotting. Leishmania with defects in the autophagy pathway, either overexpressing a dominant-negative VPS4, important in endosomal sorting pathways, 21 or lacking the major lysosomal peptidases CPA and CPB, 20 are unable to fully differentiate, in addition to being unable to survive prolonged starvation. These data show that autophagy is important for successful parasite differentiation, presumably because it is required for protein turnover during the cellular remodeling that occurs throughout the differentiation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also shown was that the absence of the cpb genes resulted in a shift in the immune response from predominantly Th2 immune response (wild-type) to the Th1 response, normally observed when the CPB isoenzymes are present [133]. It has also been suggested that in L. mexicana these enzymes are vital for autophagy and differentiation of the parasite [136]. Recently, our group described that drug-induced Leishmania autophagy is accompanied by enhanced cpb expression [137].…”
Section: Cysteine Peptidasesmentioning
confidence: 99%